Iowa Ornithologists' Union, Quarterly field report, fall 1984 - Newlon, Michael C.et al; Iowa Ornithologists' Unionet al (1984)
Iowa Ornithologists' Union, Quarterly field report, fall 1984, was compiled by Michael C. Newlon. The most important find of the season was a Rufous Hummingbird seen at a feeder in Chester, Iowa, the first state record of this species. Contex - flatbed